IN VITRO ANTIOXIDANT ACTIVITY OF DIFFERENT SUBSTITUTED BENZILIC ACID USING 2,2-DIPHENYL-1-PICRYL HYDRAZYL RADICAL, ABTS ASSAY METHOD - R, Sudha; Kanakam, Charles C; G, Nithya (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objectives: The aim of this study is to investigate the antioxidant activity of different substituted benzilic acid using DPPH assay and ABTS methods. Methods: Compounds were synthesized based on benzil-benzilic acid rearrangement. The synthesized compound was confirmed by 1HNMR, Infrared, Mass, TGA, and UV analysis. Antioxidant activity of the compound was measured by radical scavenging assay method (2,2-diphenyl-1-picrylhydrazyl) and ABTS method. Results: All synthesized compounds show moderate to extent antioxidant activity. The results for the antioxidant activity showed that the highest percentage of scavenger radicals was present in the 2'-chloro-4-methoxy-3-nitro benzilic acid. Conclusion: The result showed that better activity in 2'-chloro-4-methoxy-3-nitro benzilic acid due to the presence of electro withdrawing and electro donating group than others. Thus, it could be served as potent antioxidant. All compounds were tested for their effect on the viability of cells and results demonstrated that they are not toxic towards the cell lines used. Keywords: Synthesis, Antioxidant activity, 2, 2-diphenyl-1-picryl hydrazyl assay, ABTS assay.